Detection and Management of Hypothyroidism Following Thyroid Lobectomy: Evaluation of a Clinical Algorithm - Johner, Amanda; Griffith, Obi L.; Walker, Blair; Wood, Leanne; Piper, Hannah; Wilkins, Graeme; Baliski, Christopher; Jones, Steven J. M.; Wiseman, Sam M. (Annals of surgical oncology, 2011)
Background The objectives of this study were to determine: (1) the incidence permanent hypothyroidism after thyroid lobectomy (TL), (2) whether asymptomatic patients with mildly elevated thyrotropin (TSH) levels can be managed without thyroid hormone replacement, and (3) if the degree of lymphocytic infiltration (LI) and germinal center (GC) formation in the resected thyroid lobe correlates with the development of post-TL hypothyroidism. Methods Subjects undergoing TL between January 2006 and January 2008 at 2 centers were enrolled in the study and thyroid function was followed prospectively based on a previously published algorithm. The histology of each resected thyroid lobe was examined, and the degree of LI and GC was quantified. Results The study cohort consisted of 117 patients. Early postoperative TSH levels were significantly increased over preoperative levels ( P < .001). TSH measured at 6 months to 1 year postoperatively, while still significantly increased over preoperative levels ( P < .001), was also significantly reduced ( P = .006) compared with early postoperative levels. Of the patients who presented with early postoperative hypothyroidism, 69.2% recovered to normal levels without intervention. The overall incidence of early postoperative hypothyroidism was 21.6%, and permanent hypothyroidism was 7.8%. A high degree of LI and GC correlated with a significantly higher mean TSH level ( P = .003). Conclusions The incidence of hypothyroidism following TL is low, and a significant proportion of individuals who become biochemically hypothyroid will demonstrate only a transient elevation in their TSH levels. As well, individuals with LI, or GC formation, within their resected thyroid lobe may be at increased risk for post-TL hypothyroidism.